Waste age - National Solid Wastes Management Association (Intertec Pub, 1970)
"The official magazine of Waste Expo."
Keywords: Environmental protection : Periodicals; Refuse and refuse disposal : Law and legislation : Periodicals; Recycling (Waste, etc.) : Periodicals; Refuse and refuse disposal : Periodicals; Waste products : Periodicals; Environnement : Protection : Périodiques; Déchets : Élimination : Droit : Périodiques; Recyclage (Déchets, etc.) : Périodiques; Déchets : Élimination : Périodiques; Déchets : Périodiques; Environmental protection; Recycling (Waste, etc.); Refuse and refuse disposal; Refuse and refuse disposal : Law and legislation; Waste products